2020
DOI: 10.1002/essoar.10504277.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling Multiphase Flow Within and Around Deformable Porous Materials: A Darcy-Brinkman-Biot Approach

Abstract: Multiphase flow in deformable porous media is a ubiquitous phenomenon with important implications in many energy and environmental technologies including geologic CO 2 sequestration, soil bioremediation, water treatment, enhanced biochemical production, nuclear waste disposal, and battery technology (Bächer

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 288 publications
0
1
0
Order By: Relevance
“…As such, the inherent assumptions of these models should be adhered to. The complete numerical implementation of the solver, its validations, and the cases shown within this study can be found within the open-source simulation package "hybridBiotInterFoam" [33].…”
Section: Modeling Frameworkmentioning
confidence: 99%
“…As such, the inherent assumptions of these models should be adhered to. The complete numerical implementation of the solver, its validations, and the cases shown within this study can be found within the open-source simulation package "hybridBiotInterFoam" [33].…”
Section: Modeling Frameworkmentioning
confidence: 99%